2018
DOI: 10.1002/adma.201706098
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Immunotherapy Nanoparticle Improves T‐Cell Activation and Cancer Immunotherapy

Abstract: Combination immunotherapy has recently emerged as a powerful cancer treatment strategy. A promising treatment approach utilizes coadministration of antagonistic antibodies to block checkpoint inhibitor receptors, such as antiprogrammed cell death-1 (aPD1), alongside agonistic antibodies to activate costimulatory receptors, such as antitumor necrosis factor receptor superfamily member 4 (aOX40). Optimal T-cell activation is achieved when both immunomodulatory agents simultaneously engage T-cells and promote syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 38 publications
1
118
0
2
Order By: Relevance
“…[145] The DINP significantly elevated the rate of T cell activation and showed superior antitumor effect in B16F10 melanoma model and 4T1 breast cancer model compared with treatment with the two free antibodies. A dual immunotherapy nanoparticle (DINP) conjugating anti-PD-1 Ab and T cells agonist antitumor necrosis factor receptor superfamily member 4 (aOX40) was developed to ensure that T cells could simultaneously bind the two agents.…”
Section: Doi: 101002/advs201900101mentioning
confidence: 91%
See 1 more Smart Citation
“…[145] The DINP significantly elevated the rate of T cell activation and showed superior antitumor effect in B16F10 melanoma model and 4T1 breast cancer model compared with treatment with the two free antibodies. A dual immunotherapy nanoparticle (DINP) conjugating anti-PD-1 Ab and T cells agonist antitumor necrosis factor receptor superfamily member 4 (aOX40) was developed to ensure that T cells could simultaneously bind the two agents.…”
Section: Doi: 101002/advs201900101mentioning
confidence: 91%
“…[67] To achieve precise and controlled drug delivery, smart nanoparticles with more complex structures and specific drug release properties are also being produced according to the hallmarks of TME, such as weak acidic pH (6.5-6.8), high level of glutathione and hydrogen peroxide (H 2 O 2 ), and disorder of proteinases production, such as matrix metalloproteinase-2 (MMP-2). HDL-mimicking nanodisc Patient-derived neoantigen and cholesterol-modified CpG -- [135] PLGA NP OVA, Pam3Csk4, and Poly(I:C) CD40 on DCs - [136] Chitosan nanoparticle Cell lysate from B16 melanoma Mannose receptor on DCs - [38] Lipo-CpG micelle CpG Albumin hitchhiking - [137] γPGA-based CNNP OVA and poly(I:C) -- [138] PLGA-based AC-NP --- [139] mBiNE CRT HER-2 on tumor cells - [140] T cell activation DMAEMA, PAA, and butyl methacrylate OVA -pH [134] polyPAA OVA -pH [133] CNT MHC1 peptide, anti-CD28, and PLGA NPs encapsulating IL-2 and magnetite -- [141] Magnetic nanocluster MHC1-OVA, anti-CD28, and leukocyte membrane fragments Magnetic navigation - [128] PD-1 receptor-expressing NV --- [142] PEG-PLA NP CTLA-4 siRNA -- [143] Platelet-derived microparticle Anti-PD-L1 Ab -- [144] PEG-PLGA NP Anti-PD-1 Ab and aOX40 -- [145] Super-paramagnetic iron oxide nanoparticle Anti-PD-L1 Ab, anti-CD3/anti-CD28 Ab, fucoidan, and dextran Magnetic navigation - [129] Regulation of TME PLGA NP core with lipid shell Imatinib Nrp1 receptor on Tregs - [43] CDNP consisting of CD and lysine R848 -- [146] NV derived from type 1 macrophage --- [147] Carboxyl-functionalied and aminofunctionalized polystyrene nanoparticle --- [148] Super-paramagnetic iron oxide --- [149] Ferumoxytol --- [150] HDL NP -Scavenger receptor B1 on MDSCs - [151] PEGylated LNC lmGem -- [152] LPH NP HMGA1 siRNA Sigma receptor on tumor cells - [153] LCP NP TGF-β siRNA, tumor antigen, and CpG -- [154] PEG-PLGA NP SD-208 PD-1 on T cells - [155] Nanoparticle assembled from DEAP molecule, PD-L1 antagonist, NGL919, and a substrate peptide of MMP-2 -pH and MMP-2 …”
Section: Doi: 101002/advs201900101mentioning
confidence: 99%
“…The authors revealed the treatment synergized with anti‐programmed cell death protein 1 (PD‐1) (a checkpoint inhibitor) and led to a prominent abscopal effect. The same group later used PLGA nanoparticles to codeliver anti‐PD‐1 and anti‐OX40 (an agonistic antibody to activate costimulatory receptors) to improve treatment outcomes in two melanoma models . Also in 2017, Goldberg and co‐workers developed PLGA nanoparticles decorated with anti‐PD‐1 to target T cells as well as release R848 (resiquimod, a TLR7/8 agonist) and SD‐208 (a transforming growth factor‐β (TGF‐β) receptor inhibitor) to block the immunosuppressive effects of TGF‐β and potentiate an antitumor response .…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…By the AC‐NP, his colleagues, Mi et al, attempted to deliver anti‐PD‐1 and anti‐OX‐40 to block checkpoint inhibitor receptors and induce T cell activation, respectively. The results showed that both therapeutic efficacy and immune memory were significantly enhanced, and higher T cell activation rates than free antibodies were elicited in vitro (Mi et al, ).…”
Section: Functional Nanomaterials For Delivering Cancer Nanovaccinementioning
confidence: 99%